On Cognitive Aspect in D. Santayana’s Philosophy - Dėgesys, Liutauras (Problemos, 1982)
D. Santayana’s philosophy in the context of American critical realism is observed. The author of the article considers the latter to be an attempt to rationalize the belief, based on common sense, in the objectivity of the real world. The subdivision of reality into existences and essences as well as the presupposed possibility of reducing theory to facts gives birth to the theory of scepticism which, being based on the animal belief, implies a two-fold cognitive relation. Gnoseological explication and methodological groundlessness of the above approach is discussed.